Ion‐Selective Microporous Polymer Membranes with Hydrogen‐Bond and Salt‐Bridge Networks for Aqueous Organic Redox Flow Batteries. Issue 12 (5th February 2023) - Wang, Anqi; Tan, Rui; Liu, Dezhi; Lu, Jiaxin; Wei, Xiaochu; Alvarez‐Fernandez, Alberto; Ye, Chunchun; Breakwell, Charlotte; Guldin, Stefan; Kucernak, Anthony R.; Jelfs, Kim E.; Brandon, Nigel P.; et al.
Abstract: Redox flow batteries (RFBs) have great potential for long‐duration grid‐scale energy storage. Ion‐conducting membranes are a crucial component in RFBs, allowing charge‐carrying ions to transport while preventing the cross‐mixing of redox couples. Commercial Nafion membranes are widely used in RFBs, but their unsatisfactory ionic and molecular selectivity, as well as high costs, limit the performance and the widespread deployment of this technology. To extend the longevity and reduce the cost of RFB systems, inexpensive ion‐selective membranes that concurrently deliver low ionic resistance and high selectivity toward redox‐active species are highly desired. Here, high‐performance RFB membranes are fabricated from blends of carboxylate‐ and amidoxime‐functionalized polymers of intrinsic microporosity, which exploit the beneficial properties of both polymers. The enthalpy‐driven formation of cohesive interchain interactions, including hydrogen bonds and salt bridges, facilitates the microscopic miscibility of the blends, while ionizable functional groups within the sub‐nanometer pores allow optimization of membrane ion‐transport functions. The resulting microporous membranes demonstrate fast cation conduction with low crossover of redox‐active molecular species, enabling improved power ratings and reduced capacity fade in aqueous RFBs using anthraquinone and ferrocyanide as redox couples. Abstract : High‐performance ion‐selective polymer membranes are fabricated from blends of carboxylate‐ and amidoxime‐functionalized polymers of intrinsic microporosity by exploiting inter‐/intrachain hydrogen‐bond and salt‐bridge interactions. They demonstrate fast ion conduction with low crossover of redox‐active molecules, enabling improved power rating and stable cycling performance in aqueous organic redox flow batteries.